Comparison of clinical efficacies of sodium ascorbyl phosphate, retinol and their combination in acne treatment - C. Ruamrak (2018)
Acne vulgaris impairs the appearance of an individual and causes psychological irritation. Inflammatory acne lesion is caused by multifactor incorporates in each step of acne pathogenesis. In an attempt to archive inflammatory lesion treatment with the promise of prevention of acne vulgaris, randomized and double-blind studies on the comparison of the efficacies of topical formulations containing 5% sodium ascorbyl phosphate (SAP) and 0.2% retinol, separately as well as in combination application, were conducted. The resulting data showed that SAP reduced the inflammatory lesion by 20.14% and 48.82% within 4 and 8 weeks respectively. Application of the formulation containing retinol slightly improved the treatment efficacy as the lesion reduced by 21.79% and 49.50% after 4 and 8 weeks respectively. The combination treatment significantly reduced the inflammatory lesion by 29.28% after 4 weeks and 63.10% after 8 weeks of application. The most effective treatment was by using the combination of 5% SAP and 0.2% retinol, which incorporated the synergistic effects on lipid peroxidation and sebaceous gland function in addition to the enhancement of SAP permeability by the desquamation of stratum corneum influenced by retinol, keratin plug removal and anti-inflammatory effect of retinol. This study promises for the development of cosmetic products to overcome aesthetic and psychological problems caused by acne vulgaris. © 2009 The Authors.